Relationship Between Altimetric Quality and Along-Track Spatial Resolution for iGNSS-R Sea Surface Altimetry: Example for the Airborne Experiment - Liu, Zongqiang; Zheng, Wei; Wu, Fan; Kang, Guohua; Sun, Xuezhi; Wang, Qiang (Frontiers in Earth Science, 2021)
The altimetric quality and the along-track spatial resolution are the key parameters to characterize the performance of interferometric global navigation satellite systems reflectometry (iGNSS-R) sea surface altimetry, and they are closely related through the signal processing time. Among them, the quality of sea surface height (SSH) measurement includes the precision and the accuracy. To obtain higher altimetric quality in the observation area requires longer signal processing time, which in turn will cause a loss of spatial resolution along the track. On the contrary, obtaining a higher along-track spatial resolution requires more intensive sampling, which ultimately leads to unsatisfactory altimetric quality. Taking the airborne iGNSS-R observation data as an example, this research analyzed the relationship between the altimetric quality and the along-track spatial resolution from the perspectives of the precision and the accuracy. The results show that the reduction of the along-track spatial resolution will improve the altimetric quality, in which the precision at the range between 0.16 m and 1.13 m, and the accuracy at the range between 0.28 m and 0.73 m. However, this change is not linear, and the improvement of altimetric quality will slow down with the decrease of along-track spatial resolution. The research results in this paper can provide a scientific reference for the parameter balance configuration of future spaceborne iGNSS-R altimetry missions.